SCN1A Gene Mutations in Severe Infantile Myoclonic Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Ten novel mutations of SCN1A were found in in a pair of monozygotic twins and 12 unrelated Japanese infants with severe myoclonic epilepsy in infancy (SMEI) examined at the Brain Science Institute, Saitama; and National Epilepsy Center, Shizuoko, Japan.